(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the reality of using alternative assessment methods (portfolio, self-assessment) in evaluating the performance of students at the Faculty of Physical Education and Sports Sciences at Al-Jafara University. The study adopted the descriptive survey approach, and a questionnaire was applied to a sample of (20) faculty members. The results showed that the degree of use of alternative assessment methods was medium to low, with the arithmetic mean for portfolio use being (3.34) and for self-assessment (3.18). The results also revealed main obstacles represented by the need for professional development programs (4.47), student density (4.37), and lack of course time (4.30). While positive trends towards the benefits of these methods were shown, with the arithmetic mean of the trends axis being (3.87). The study recommended providing professional development programs, preparing a unified guide, and providing the necessary technical support to activate the use of these methods.